1990
DOI: 10.1073/pnas.87.17.6604
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral tolerance in mice expressing a liver-specific class I molecule: inactivation/deletion of a T-cell subpopulation.

Abstract: We previously demonstrated that C3H/HeJ transgenic (TG) mice that express a laboratory-engineered class I molecule, Q1O/L, exclusively on liver parenchymal cells show no evidence of hepatic disease even after deliberate immunization. Nevertheless, these animals demonstrate cytotoxic T-lymphocyte (CTL) activity specific for Q1O/L, although it is less than that obtained from non-TG littermates. We now show that this decrease in CTL activity is not a reflection of a decrease in precursors, since both TG and norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…The reduced alloreactivity of residual T cells from doubly transgenic mice is in agreement with studies that show a reduced T-cell responsiveness associated with peripheral expression of self-antigen (2)(3)(4)(5)(6) …”
supporting
confidence: 75%
See 2 more Smart Citations
“…The reduced alloreactivity of residual T cells from doubly transgenic mice is in agreement with studies that show a reduced T-cell responsiveness associated with peripheral expression of self-antigen (2)(3)(4)(5)(6) …”
supporting
confidence: 75%
“…4). At birth (5,6,9,11,(19)(20)(21)(22)(23)(24). Likewise, EL singly transgenic mice did not develop spontaneous autoimmunity in exocrine pan- creas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to naïve splenocytes, those that were primed and activated from nontransgenic animals caused a periportal infiltrate after transfer into Q10/H-2L d -bearing transgenic mice. The study concluded that hepatocytes expressing a neoantigen on their surface can provide antigen-specific T cell tolerance [53,54]. It is not quite clear whether tolerance induction in this model results from T cell anergy or deletion because the fate of antigen-specific T cells cannot be followed in vivo properly.…”
Section: Transgenic Aih Models With Defined Model Antigensmentioning
confidence: 99%
“…Among the first studies to use a liver-specific neoantigen were those performed by Jones-Youngblood et al [53], when the MHC I-like molecule Q10 was expressed as a fusion protein with H-2L d on the surface of hepatocytes [54]. No signs of spontaneous hepatitis were seen.…”
Section: Transgenic Aih Models With Defined Model Antigensmentioning
confidence: 99%